Influence of Dietary Supplementation of Dried Purslane (Portulaca oleracea L.) Powder on Growth Performance and Susceptibility of Chicken Thigh Muscle to Lipid Oxidation During Frozen Storage Conditions - Safari, Hassan; Mohit, Ardeshir; Mohiti-Asli, Maziar (Indian Journal of Animal Nutrition, 2018)
An experiment was conducted to examine the effects of dried purslane powder (DPP) supplementation to broiler diet on growth performance and susceptibility of thigh muscle to lipid oxidation during frozen storage at -20Â° C for six months. One hundred sixty one-day-old chicks were allocated in a completely randomized design into four treatments and four replicates with 10 birds in each replication. DPP was included @ 0, 2.5, 5 and 7.5% of the diet in treatments DPP0, DPP2.5, DPP5 and DPP7.5, respectively. The feed intake was more (P<0.05) in broilers given DPP than the control group. The daily weight gain increased (P<0.05) due to increasing DPP content in diet. Broilers fed 5 and 7.5% DPP had better (P<0.05). feed conversion ratio than those in the control group. Susceptibility of meat to lipid oxidation was determined by measuring thiobarbituric acid reactive substances (TBARS) value and pH of thigh muscle after storing for 2, 4 and 6 months in freezer. Results demonstrated that broiler fed 5 and 7.5% of DPP had lower (P<0.05) TBARS and higher moisture content in meat than the control group. The TBARS values of meat increased and moisture content decreased by increasing storage time (P<0.05). However, meat pH was not affected. Therefore, supplementation of DPP to broiler diet resulted in better growth performance and increased meat oxidative stability during storage.